Characterization of newborns using mechanical ventilation at a neonatal unit - Andréa Lopes Barbosa; Edna Maria Camelo Chaves; Antonia do Carmo Soares Campos (Rev Rene)
This study aimed to characterize the profile of newborns (NBs) of a public neonatal unit in the city of Fortaleza using mechanical ventilation (MV). It is an exploratory-descriptive research, conducted with newborns using MV. The sample was composed of 42 NBs that remained for at least 12 hours under ventilatory assistance. The data were collected from April to July 2004, through a form. It was verified that 52.4% were males, 35.7% weighing between 1001 and 1500 grams. In relation to gestational age 35.7% were between 31 to 36 weeks. We got to the conclusion that the newborns weighing less than 1500 grams and younger than 31 weeks of gestational age, due to their lung immaturity. are the great MV users.